Reducing an Adolescent's Destructive Behavior during Bathroom Visits in a Residential Setting: Brief Report. (2nd October 2020) - Dowdy, Art; Tincani, Matt; Jessel, Joshua
ABSTRACT: As individuals with autism spectrum disorder (ASD) transition to adulthood, problem behavior may present restrictions to an independent lifestyle. In addition, problem behavior may interfere with performance of daily routines necessary for independent living. We developed a successful treatment for automatically reinforced toilet lid destruction of an adolescent with ASD during routine bathroom visits. The treatment was informed by a competing stimulus assessment (CSA) that identifies a preferred stimulus, the presentation of which is intended to compete with automatic reinforcement of problem behavior. Results indicated that access to the competing stimulus reduced the participant's toilet lid destruction while in the bathroom, and these treatment gains maintained during long term follow-up visits.